Atomistic investigation of calcium sulfonate and lithium complex grease tribofilms under severe sliding conditions. Issue 1 (2022) - Bedekar, Vikram; Mistry, Kuldeep; Voothaluru, Rohit; Qu, Jun; Poplawsky, Jonathan
Abstract: Innovative grease chemistries and additives are continuously developed to meet challenging applications such as wind energy bearings and offshore/underwater applications. The non-equilibrium and transient structures within interfacial tribofilms play an influential role in the service life of a component. Atom probe tomography and transmission electron microscopy studies were performed to investigate the tribofilms formed by lithium complex and calcium sulfonate grease thickeners. The study reveals that morphology, amorphicity, nanostructure, and atomic layering play an influential role in the exceptional wear and corrosion performance of calcium sulfonate thickeners.